2020
DOI: 10.4103/ams.ams_132_20
|View full text |Cite
|
Sign up to set email alerts
|

Role of custom-made prosthesis for temporomandibular joint replacement in unilateral ankylosis - An evaluative study

Abstract: Introduction: Ankylosis is a physically and psychologically distressing condition to a patient. The aim of this study was to evaluate the efficiency of custom-made temporomandibular joint (TMJ) prosthesis (fossa-condyle component) in patients with unilateral ankylosis in restoring the form and functions of the TMJ. Materials and Methods: This retrospective study was conducted in ten patients with unilateral TMJ ankylosis who had undergone TMJ reconstruction with custom-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Thereby, the patient results showed an aMMO ranging from 33 to 58 mm and a pMMO ranging from 35 to 59 mm, which demonstrates that these patients had a satisfactory mandibular range of motion. In most other studies, lower MMO results were found postoperatively [35,[40][41][42][43][44][45][46][47][48][49][50][51][52]. Only one prospective cohort study showed similar MMO results at the 12-month follow-up and thereafter [53].…”
Section: Discussionmentioning
confidence: 97%
“…Thereby, the patient results showed an aMMO ranging from 33 to 58 mm and a pMMO ranging from 35 to 59 mm, which demonstrates that these patients had a satisfactory mandibular range of motion. In most other studies, lower MMO results were found postoperatively [35,[40][41][42][43][44][45][46][47][48][49][50][51][52]. Only one prospective cohort study showed similar MMO results at the 12-month follow-up and thereafter [53].…”
Section: Discussionmentioning
confidence: 97%
“…Among TMJ reconstruction options are alloplastic total joint replacements, reconstructions with a condylar head prosthesis, non-vascularized bony flaps, and microvascular free flaps [ 10 , 11 ] Reconstruction bars with condylar heads are usually used as an interim treatment due to the high complication risk involved like plate fracture and/or exposure, facial nerve damage, and erosion into the external auditory meatus or skull base [ 7 , 8 ]. Total joint replacement prostheses like TMJ Concepts work well in cases with completed bone growth, benign tumors, and defects that do not have a large soft tissue component [ [10] , [11] , [12] ]. The use of free bone grafts for defects involving the TMJ has been widely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Alloplastic reconstruction of the condyles with a recon bar and condylar head has been historically associated with several complications like plate fracture and sensory disturbances [ [7] , [8] , [9] ]. Custom and stock TMJ prostheses work well but have limitations depending on the amount of bone and soft tissue that is being reconstructed simultaneously [ [10] , [11] , [12] ]. Additionally, they are not ideal in wounds with poor recipient beds due to multiple prior surgeries, infection, or irradiation [ [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%